2017
DOI: 10.1126/sciadv.aao1874
|View full text |Cite
|
Sign up to set email alerts
|

Increased weight gain by C-section: Functional significance of the primordial microbiome

Abstract: Mice born by C-section developed increased body weight and lacked microbiota developmental changes observed in control mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 26 publications
6
55
0
Order By: Relevance
“…At the genus level, our results reflected that the relative abundances of Bifidobacterium, Bacteroides, Alistipes, Lachnospiraceae NK4A136 group and Alloprevotella decreased while that of Parabacteroides, Eubacterium xylanophilum group, GCA-900066575, Lachnoclostridium, Lachnospiraceae UCG-006 and Romboutsia increased in the HFD group compared with the control group. In line with our results, earlier studies found that the abundances of Bifidobacterium (Zhu et al, 2018), Bacteroides (Zhang et al, 2015;Martinez et al, 2017), Alistipes (Zhu et al, 2018), Lachnospiraceae NK4A136 group , and Alloprevotella were negatively correlated with obesity, and the abundances of Parabacteroides (Lieber et al, 2018;Zhao et al, 2018), Eubacterium xylanophilum group , GCA-900066575 , Lachnoclostridium (Zhao et al, 2017b), Lachnospiraceae UCG-006 (Kang et al, 2019), and Romboutsia (Zhao et al, 2018) were positively correlated with obesity. Bifidobacterium, a beneficial microbial species, producing lactic acid and acetic acid, can reduce intestinal pH and inhibit the growth of various detrimental bacteria to maintain intestinal health (Wang R. et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…At the genus level, our results reflected that the relative abundances of Bifidobacterium, Bacteroides, Alistipes, Lachnospiraceae NK4A136 group and Alloprevotella decreased while that of Parabacteroides, Eubacterium xylanophilum group, GCA-900066575, Lachnoclostridium, Lachnospiraceae UCG-006 and Romboutsia increased in the HFD group compared with the control group. In line with our results, earlier studies found that the abundances of Bifidobacterium (Zhu et al, 2018), Bacteroides (Zhang et al, 2015;Martinez et al, 2017), Alistipes (Zhu et al, 2018), Lachnospiraceae NK4A136 group , and Alloprevotella were negatively correlated with obesity, and the abundances of Parabacteroides (Lieber et al, 2018;Zhao et al, 2018), Eubacterium xylanophilum group , GCA-900066575 , Lachnoclostridium (Zhao et al, 2017b), Lachnospiraceae UCG-006 (Kang et al, 2019), and Romboutsia (Zhao et al, 2018) were positively correlated with obesity. Bifidobacterium, a beneficial microbial species, producing lactic acid and acetic acid, can reduce intestinal pH and inhibit the growth of various detrimental bacteria to maintain intestinal health (Wang R. et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…; Martinez et al . ). Intrapartum antibiotics can lead to increased abundance of Bacteroides and Enterobacteria and reduction of Bacteroidetes in the neonatal gut (Li et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Martinez et al . ), as well as CS effectively bypassing normal microbial seeding by maternal vaginal and intestinal flora.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sex of the offspring seems also to be of importance with female offspring being more affected. However, this evidence was gathered from animal models (Martinez et al, 2017) and more research is needed to ascertain if this also happens in humans.…”
Section: Introductionmentioning
confidence: 99%